Financial Feasibility Analysis and Circular Economy Capitalization Strategy: A Case Study of Salmon Skin Waste Processing MSMEs (Salmontok) in Bali - Timothy Marthin; Bernard T. Widjaja (Jurnal Indonesia Sosial Sains, 2026)
The food MSME sector in Indonesia faces major challenges in terms of operational efficiency and investment visibility. This research aims to formulate a comprehensive business development plan within a period of five years, with a focus on operational transformation and strengthening the financial structure. This study used a descriptive qualitative approach with the type of applied research. Primary data was obtained through interviews, direct observations, and consumer surveys, while secondary data was obtained from the scientific literature. The financial feasibility analysis was carried out using the Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, and Break-Even Point (BEP) indicators. The results of the study show that the transformation towards "Smart-Manufacturing MSMEs" through drying mechanization (digital industrial dehydrators) is able to significantly increase production capacity, from 4,500 units to 20,000 units per month, while increasing time efficiency by 20%. From the financial aspect, the initial investment of IDR 850,000,000 is projected to generate turnover growth from IDR 1.2 billion in the first year to IDR 8.5 billion in the fifth year. Valuation analysis shows a positive NPV value of IDR 231,571,868, IRR of 33.00% (above the discount rate of 25%), and a Payback Period of 3 years and 9 months. Overall, Salmontok’s business development plan is declared FEASIBLE to implement because it is able to create sustainable economic added value, strengthen brand equity, and have a managed risk profile.